Observation of multiple steady states with engineered dissipation - Li Li; Tong Liu; Xue-Yi Guo; He Zhang; Silu Zhao; Zheng-An Wang; Zhongcheng Xiang; Xiaohui Song; Yu-Xiang Zhang; Kai Xu; Heng Fan; Dongning Zheng (npj Quantum Information)
Abstract Simulating the dynamics of open quantum systems is essential in achieving practical quantum computation and understanding novel nonequilibrium behaviors. However, quantum simulation of a many-body system coupled to an engineered reservoir has yet to be fully explored in present-day experiment platforms. In this work, we introduce engineered noise into a one-dimensional ten-qubit superconducting quantum processor to emulate a generic many-body open quantum system. Our approach originates from the stochastic unravellings of the master equation. By measuring the end-to-end correlation, we identify multiple steady states stemmed from a strong symmetry, which is established on the modified Hamiltonian via Floquet engineering. Furthermore, we investigate the structure of the steady-state manifold by preparing initial states as a superposition of states within different sectors on a five-qubit chain. Our work provides a manageable and hardware-efficient strategy for the open-system quantum simulation.